The impact of Service Performance on Customer Satisfaction and Customer Loyalty During Covid-19 Pandemic: A Case Study of Bank BTN - Christian Kuswibowo (Sekolah Tinggi Manajemen IPMI, 2022)
This study is to analyze the impact of service performance and customer satisfaction as a moderating variable on customer loyalty of Bank BTN (Bank Tabungan Negara) in COVID-19 Pandemic. The object of this research is the customers of Bank BTN. This research was conducted on 200 respondents using a quantitative descriptive approach. Determination of sample size using purposive sampling technique, purposive sampling technique is a technique of determining the sample with certain considerations. Methods of data collection using survey methods, with the research instrument is a questionnaire. The approach used in this research is the Structural Equation Model with the Smart-PLS analysis tool. This study proves that service performance has a positive and significant effect on customer satisfaction, service performance has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty. The implication of this study is to encourage the industry to improve and maintain their service performance especially during this pandemic to increase their customer satisfaction and customer loyalty level.